(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This study presents a direct comparison between fractional-order PID (FOPID) and classical PID controllers using a novel regularization-based tuning technique originally developed for integral-order controllers and adapted for fractional-order applications. Although the optimization problem is not convex by its nature, the objective function sweep results indicate the weak convexity of the problem, which validates the proposed method. Simulation results illustrate that the integral order (λ) is typically close to 1, which suggests that there is little advantage in integrating the fractional order in the conventional case. But improvements were noted in systems with positive zeros (far from the origin), long dead times, and high order. In these cases, FOPID carriers reduced ITAE by 20–30%, reduced settling time by 10–30%, and increased phase margin by up to 30%, further demonstrating better performance and robustness. The advantages stem from the softer polynomial kernel of the fractional derivative, which provides more flexible control in systems with intricate or suspended dynamics than classical PID controllers.